2016
DOI: 10.12657/folmal.024.022
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive biology and growth of two Vallonia species in laboratory conditions (Gastropoda: Eupulmonata: Valloniidae)

Abstract: Folia Malacologica is funded by the Ministry of Science and Higher Education, Republic of Poland under agreement no. 646/P-DUN/2016 allocated to the activities of disseminating scienceFolia Malacol. 24(4): 265-273 http://dx.abstract: Reproduction and growth of Vallonia pulchella (O. F. Müller) and V. costata (O. F. Müller) were studied in laboratory conditions. Their ellipsoid and singly laid eggs are among the smallest heavily calcified (mean size 0.68×0.67×0.52 and 0.69×0.67×0.54 mm in V. pulchella and V. co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The negative response of large snails, reaching later sexual maturity and having more offspring, is most probably explained by the preference of large helicid snails for less complex habitats. The number of eggs (and by default the number of offspring) is known to be small in minute species with short lifespans occurring in leaf litter 51 53 . Baur 51 issues two hypotheses concerning this convergence: it can be the result of specific natural selection processes in the leaf litter microhabitat or, a general constraint caused by the very small size of the animals.…”
Section: Discussionmentioning
confidence: 99%
“…The negative response of large snails, reaching later sexual maturity and having more offspring, is most probably explained by the preference of large helicid snails for less complex habitats. The number of eggs (and by default the number of offspring) is known to be small in minute species with short lifespans occurring in leaf litter 51 53 . Baur 51 issues two hypotheses concerning this convergence: it can be the result of specific natural selection processes in the leaf litter microhabitat or, a general constraint caused by the very small size of the animals.…”
Section: Discussionmentioning
confidence: 99%
“…There have been few publications on the results of aut-and demecological research on the land snail V. pulchella. In the 1930s, research was carried out on the reproduction of this mollusc (Whitney, 1937(Whitney, , 1941, which was continued in this century (Kuźnik-Kowalska & Proćkow, 2016). It was revealed that the density of V. pulchella is affected by many soil physico-chemical properties, especially calcium and magnesium concentration and pH of water extract (Hermida et al, 1993(Hermida et al, , 2000.…”
Section: Introductionmentioning
confidence: 99%
“…Like kiwis (Bain, 2018), some small land snails need moist environments; are not agile; have unexpectedly long lifespans (Finch, 1994, p. 13;Kuźnik-Kowalska & Proćków, 2016); lay relatively large eggs with little individual variation (Baur, 1994); and invest resources in large offspring with better survival rates (Baur & Raboud, 1988). Perhaps kiwis, and snails with this list of characteristics, which I will call the "Kiwi Syndrome", have been exposed to evolutionary pressures that include low egg predation, heavy predation on the young, and a minimal viable size for hatchlings, forcing small snails to invest in relatively large offspring at the cost of reduced fecundity.…”
mentioning
confidence: 99%